The Influence of Quality Assurance and Knowledge Management on Higher Education Accreditation Performance - Febriadi, Bayu; Putra, Pandu Pratama; Syam, Febrizal Alfarasy (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
With the issuance of Permendikbud No 53 Tahun 2023 concerning the accreditation transformation mechanism and Quality Assurance System for higher education, it is hoped that existing study programs at state universities and private universities can adjust the direction of accreditation performance policies and Higher Education Performance Indicators. Lancang Kuning University currently has 32 study programs consisting of 11 new study programs that still have accreditation with minimum scores. So it is hoped that the study program will respond well to higher education accreditation performance. This is in line with the expectations of Lancang Kuning University to ensure a culture of quality in achieving the vision and mission of higher education. The method used in this research is quantitative by determining Quality Assurance and Knowledge Management variables in influencing the accreditation performance of universities and study programs. Quality Assurance 0.790 coefficient influences accreditation performance and Knowledge Management influence 0.778 coefficient influences the accreditation performance of Lancang Kuning University.